Clustering web pages based on doc type structure in a distributed manner - Kader, Kazi Samiul; Nawar, Sagufa; Ananna, Nusrat Sharmin; Khan, Sarah (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2015.